Pemberdayaan Masyarakat melalui Coaching Clinic sebagai Model Pembinaan Sepak Bola Berkelanjutan - Hidayat, Joni Taufik; Sudirman, Sudirman; Diuli, Muhammad Reza Pratama; Latembo, Firman; Putra, Ray Mandala; Haryanto, Arif (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The Sport Science–based Coaching Clinic Program at the Duminanga Village Football School (SSB) was implemented to address key challenges, including low coaching competence, limited training facilities, and weak organizational management, which hinder effective youth football development. This program aimed to enhance coaches’ capacity, athletes’ training quality, and organizational governance through an integrated sport science approach. The program employed a participatory and educational approach, consisting of training sessions, mentoring, and the application of scientifically based training methods tailored to the initial conditions of the SSB. Program effectiveness was evaluated by comparing conditions before and after implementation, focusing on coach competence, athlete performance, and organizational management. The results indicate improvements in coaching quality, athlete motivation and training outcomes, as well as strengthened organizational structures and supporting facilities. Overall, the program proved effective in reinforcing community-based football development and has the potential to be replicated in other football schools with similar characteristics.